How will International Business Survive the Fourth Industrial Revolution? - Danko, Taras (My University, 2021)
The article contains conceptual outlines of the key capabilities that international companies have to develop in order to remain resilient and competitive in the era of the Fourth Industrial Revolution.
Keywords: international business; fourth industrial revolution; management; organizational resilience; capabilities; corporate competitiveness